Electrocardiographic characteristics associated with late gadolinium enhancement and prognostic value in patients with dilated cardiomyopathy - Chayanopparat, Punyanuch; Boonyasirinant, Thananya; Prapan, Natthaporn; Phoopattana, Supamongkol; Kaolawanich, Yodying (Frontiers in Cardiovascular Medicine, 2023)
Background: Late gadolinium enhancement (LGE) cardiac magnetic resonance (CMR) imaging has emerged as an important tool for assessment of patients with dilated cardiomyopathy (DCM).Electrocardiography (ECG) is an accessible, reproducible, low-cost diagnostic and prognostic tool. This study aimed to investigate the ECG characteristics associated with LGE, as well as to assess the prognostic significance of ECG in patients with DCM.[LVEF]<50%) between 2011 and 2020 were included. Multivariable analysis was conducted to evaluate ECG predictors associated with LGE. Receiver operating characteristic (ROC) analysis was performed to assess the diagnostic performance of ECG in combination of clinical data and LVEF for LGE. Two composite outcomes were also assessed among patients with and without ECG predictors: 1) sudden cardiac death (SCD), sustained ventricular arrhythmia, or appropriate implantable cardioverter-defibrillator (ICD) therapy, and 2) all-cause death or hospitalization for heart failure.Results: A total of 422 patients, with a mean age of 59.5±16.3 years (58.3% male), were included. LGE was present in 169 (40%) of the patients. Multivariable analysis identified lateral inverted T-waves, intraventricular conduction delay, low voltage, and fragmented QRS as independent predictors of LGE. ROC analysis showed a significant increase in the area under the curve (AUC) when ECG predictors of the four aforementioned characteristics were added to the clinical-LVEF model (AUC 0.66, 95% CI 0.59-0.71 versus 0.72, 95% CI 0.67-0.78, p=0.003).During a median follow-up of 2.7 years (IQR 0.8, 5.2), 16 events of SCD, sustained ventricular arrhythmia, or appropriate ICD therapy, and 70 events of all-cause death or hospitalization for heart failure occurred. ECG predictors were independently associated with SCD, sustained ventricular arrhythmia, or appropriate ICD therapy (HR 6.61, p<0.001).However, ECG predictors were not associated with all-cause death or hospitalization for heart failure (HR 1.22, p=0.39).In patients with DCM, lateral inverted T-waves, intraventricular conduction delay, low voltage, and fragmented QRS were independently associated with LGE. Additionally, these ECG predictors had prognostic value for predicting SCD, sustained ventricular arrhythmia, or appropriate ICD therapy, assisting clinicians in stratifying SCD risk and identifying primary prevention ICD implantation candidates.